Adolescent Girls' Knowledge About Iron Tablets: A Descriptive Study - Sariani, Sariani; Murtiningsih, Dewi; Sri Mulati, Triwik (Poltekkes Kemenkes Surakarta, 2024)
Background: Adolescent girls are a group that is vulnerable to anemia due to increased iron requirements during growth and menstruation. Lack of knowledge about the importance of iron tablet consumption is one of the factors causing low compliance in anemia prevention. This study aims to determine the knowledge of adolescent girls about iron tablets at MTs Muhammadiyah Special Program Bayat, Klaten. Methods: A quantitative descriptive design with total sampling technique was used. The sample consisted of 50 respondents who met the inclusion criteria. The research instrument used a structured questionnaire that had been tested for validity and reliability. Data analysis was performed univariately with frequency distribution using statistical data processing software. Results: The results showed that most adolescent girls had a good level of knowledge about iron tablets, with 34 respondents (68%). Based on age characteristics, good knowledge was more prevalent among early adolescents, with 26 respondents (68%), while based on grade level, the majority were in grade VII, with 15 respondents (64%). The most common source of information was teachers, with 18 respondents (82%). Conclusion: Most female adolescents at MTs Muhammadiyah Program Khusus Bayat have good knowledge about iron tablets. The recommendation from this study is the need to improve health education through UKS activities and regular counseling by health workers and teachers so that adolescents better understand the importance of regular iron tablet consumption to prevent anemia.